2019
DOI: 10.2139/ssrn.3402071
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Antagonist Modulation of TRPV2 by Piperlongumine Impairs Glioblastoma Progression

Abstract: The use of computational tools to identify biological targets of natural products with anticancer properties and unknown modes of action is gaining momentum. We employed self-organizing maps to deconvolute the phenotypic effects of Piperlongumine (PL) and establish a link to modulation of the human transient receptor potential vanilloid 2 (hTRPV2) channel. The structure of the PL-bound full-length rat TRPV2 channel was determined by cryo-EM. PL binds to a transient allosteric pocket responsible for a new mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Another example of natural product discovery across the taxonomic domain is showcased by searching for piperlongumine, an amide alkaloid originally isolated from the Piper genus (Piperaceae), which has a reported antitumor activity 28 ( Figure 1c ). This molecule is also currently being investigated for the treatment of glioblastoma 29 . Utilizing plantMASST, we observed that the piperlongumine MS/MS spectrum was also detected in two other botanical species: Gymnotheca chinensis Decne.…”
Section: Mainmentioning
confidence: 99%
“…Another example of natural product discovery across the taxonomic domain is showcased by searching for piperlongumine, an amide alkaloid originally isolated from the Piper genus (Piperaceae), which has a reported antitumor activity 28 ( Figure 1c ). This molecule is also currently being investigated for the treatment of glioblastoma 29 . Utilizing plantMASST, we observed that the piperlongumine MS/MS spectrum was also detected in two other botanical species: Gymnotheca chinensis Decne.…”
Section: Mainmentioning
confidence: 99%
“…For example, deep-learning algorithms have been devised to predict retrosynthetic pathways to molecules of interest [45] and design new chemical entities that can be scrutinized as hits/drug leads [46][47][48]. Also, different learning heuristics that leverage chemical structure data have been implemented to identify drug-target interactions that can be exploited in pre-clinical studies [49,50] and to design experiments [51,52].…”
Section: Machine Learning For Target Identificationmentioning
confidence: 99%
“…This appears to be a reasonable approach as an identical strategy was followed to identify the prostanoid 3 receptor (EC50 = 6 nM) and the voltage-gated Cav1.2 channel (IC50 = 6 µM) as targets for doliculide, 4, and 2, respectively [55,56]. Similarly, fragment-like alkaloids graveolinine (5), isomacroin (6), and piperlongumine (7) could be de-orphanized with SPiDER as serotonin 2B receptor (IC50 = 12 µM), platelet-derived growth factor receptor alpha (IC50 = 25 µM), and transient receptor potential channel vanilloid 2 (EC50 = 5 µM) modulators, respectively, which opens new avenues for molecular optimization in hit-to-lead programs [49,57]. More recently, SPiDER has been applied to prioritize de novo designed chemical entities fitting a predefined pharmacological profile for synthesis and experimental validation [46,58].…”
Section: Machine Learning For Target Identificationmentioning
confidence: 99%
“…A recent study using machine intelligence to screen compound libraries identified piperlongumine as a TRPV2 inhibitor. Furthermore, the study suggested that the cytotoxic effects of the compound were a result of its action on TRPV2, which is overexpressed in many cancers (Baker et al, 2019). The cryo-EM structure of rat TRPV2 in complex with piperlongumine suggested that the compound binds at the N-terminal end of the S4-S5 linker of one subunit and the S5 and S6 of the neighbouring subunit (Baker et al, 2019).…”
Section: Other Binding Sitesmentioning
confidence: 99%
“…Furthermore, the study suggested that the cytotoxic effects of the compound were a result of its action on TRPV2, which is overexpressed in many cancers (Baker et al, 2019). The cryo‐EM structure of rat TRPV2 in complex with piperlongumine suggested that the compound binds at the N‐terminal end of the S4–S5 linker of one subunit and the S5 and S6 of the neighbouring subunit (Baker et al, 2019). However, further mutagenesis and electrophysiological studies are required to validate the binding site.…”
Section: Ligand Binding Sites and Activation Mechanisms In Thermotrpv...mentioning
confidence: 99%